Settings and mechanisms for trans-cellular diapedesis - Sage, Peter T. (2009)
Immune system functions require blood leukocytes to continuously traffic throughout the body and repeatedly cross endothelial barriers (i.e., diapedese) as they enter (intravasation) and exit (extravasation) the circulation. The earliest studies to directly characterize diapedesis in vivo suggested co-existence of two distinct migratory pathways: between (para-cellular) and through (trans-cellular) individual endothelial cells. However, in the absence of conclusive in vitro observations, the latter pathway remained poorly accepted. The recent emergence of unambiguous in vitro reports of trans-cellular diapedesis has begun to illuminate mechanisms for this pathway and has renewed interest in its physiological roles. A thorough reevaluation of the existing literature reveals a large number of studies documenting significant use of the trans-cellular pathway in diverse in vivo settings. These include constitutive trafficking in bone marrow and lymphoid organs as well as upregulated extravasation in peripheral tissues during inflammation. Here we collectively summarize these in vivo observations alongside the emerging in vitro data in order to provide a framework for understanding the settings, mechanisms and roles for the trans-cellular route of diapedesis.